84.1k views
4 votes
Use the variation of parameters method to solve the DR y" + y' - 2y = 1

User Metabble
by
5.2k points

1 Answer

0 votes

Answer:


y(t)\ =\ C_1e^(-2t)+C_2e^t-t(e^(-2t))/(3)-(1)/(3)

Explanation:

As given in question, we have to find the solution of differential equation


y

by using the variation in parameter method.

From the above equation, the characteristics equation can be given by


D^2+D-2\ =\ 0


=>D=\ (-1+√(1^2+4* 2* 1))/(2* 1)\ or\ (-1-√(1^2+4* 2* 1))/(2* 1)


=>\ D=\ -2\ or\ 1

Since, the roots of characteristics equation are real and distinct, so the complementary function of the differential equation can be by


y_c(t)\ =\ C_1e^(-2t)+C_2e^t

Let's assume that


y_1(t)=e^(-2t)
y_2(t)=e^t


=>\ y'_1(t)=-2e^(-2t)
y'_2(t)=e^t

and g(t)=1

Now, the Wronskian can be given by


W=y_1(t).y'_2(t)-y'_1(t).y_2(t)


=e^(-2t).e^t-e^t(-e^(-2t))


=e^(-t)+2e^(-t)


=3e^(-t)

Now, the particular solution can be given by


y_p(t)\ =\ -y_1(t)\int{(y_2(t).g(t))/(W)dt}+y_2(t)\int{(y_1(t).g(t))/(W)dt}


=\ -e^(-2t)\int{(e^t.1)/(3.e^(-t))dt}+e^(t)\int{(e^(-2t).1)/(3.e^(-t))dt}


=\ -e^(-2t)\int{(1)/(3)dt}+(e^t)/(3)\int{e^(-t)dt}


=(-e^(-2t))/(3).t-(1)/(3)


=-t(e^(-2t))/(3)-(1)/(3)

Now, the complete solution of the given differential equation can be given by


y(t)\ =\ y_c(t)+y_p(t)


=C_1e^(-2t)+C_2e^t-t(e^(-2t))/(3)-(1)/(3)

User Bspeagle
by
4.9k points